Cancer: are transgender women at risk? - Mustapar, Nurulhasanah (Centre for Islamisation (CENTRIS), IIUM, 2024)
This chapter explores the cancer risks faced by transgender women, focusing on the potential effects of hormone therapy, surgical procedures, and other modifiable factors such as smoking and obesity. The chapter highlights the scarcity of research on cancer in transgender populations, emphasising the need for more studies to understand the prevalence and prognosis of various cancers. Specific risks related to breast cancer, prostate cancer, HPV- related cancers, and other conditions like meningiomas and prolactinomas are discussed. The importance of developing transgender-specific cancer screening guidelines and addressing healthcare disparities is underscored to improve health outcomes in this vulnerable population.